THE RELATIONSHIP BETWEEN THE STATUS OF EXCLUSIVE BREASTFEEDING WITH MOTOR DEVELOPMENT IN CHILDREN AGED 1-3 YEARS AT WORKING AREA OF TALISE PUBLIC HEALTH CENTER IN 2016 - Febriady, Ahmad; Sumarni, Sumarni; Badaruddin, Rahma (Medika Tadulako: Jurnal Ilmiah Kedokteran Fakultas Kedokteran dan Ilmu Kesehatan, 2017)
Background. Exclusive breastfeeding is giving only breast milk without any liquid or solid food except vitamin, mineral, or medication in the form of drops or syrup until the age of 6 months. This study aims to determine the relationship between the status of exclusive breastfeeding with motor development in children aged 1-3 years at working area of Talise Public Health Center.Methods. The study was observational analytic with cross sectional approach. The samples used were 92 children aged 1-3 years, with a purposive sampling technique. The results of this study were statistically tested by chi-square test on the error rate 10% using a computer software program. Result. In this research showed that under-five children who are not receive exclusive breastfeeding and motor development that deviates as much as 15 children (26.8%), under-five children who are not receive exclusive breastfeeding and motor development that dubious as much as 29 children (51.8%) and under-five children who are not exclusive breastfeeding and appropriate motor development as many as 12 children (21.4%). In under-five children with exclusive breastfeeding and motor development that deviates as much as 0 children (0%), under-five children who are receive exclusive breastfeeding and motor development that dubious as much as 1 children (2.8%), as well as under-five children who are receive exclusive breastfeeding and appropriate motor development as many as 35 children (97, 2%). Conclusion. There was a significant relationship between the status of exclusive breastfeeding with motor development in children aged 1-3 years at working area of Talise Public Health Center in 2016. Keywords : Exclusive Breastfeeding, Motor Development Latar Belakang. ASI eksklusif adalah pemberian hanya ASI saja tanpa cairan atau makanan padat apapun kecuali vitamin, mineral, atau obat dalam bentuk tetes atau sirup sampai usia 6 bulan. Penelitian ini bertujuan untuk mengetahui hubungan antara status pemberian ASI eksklusif dengan perkembangan motorik pada anak usia 1 – 3 tahun diwilayah kerja Puskesmas Talise.Metode. Penelitian observasional analitik korelatif dengan Pendekatan Cross Sectional Study. Jumlah sampel yang digunakan adalah 92 balita usia 1-3 tahun, dengan teknik purposive sampling. Hasil penelitian ini diuji secara statistik dengan uji chi square pada tingkat kesalahan 10% menggunakan program software komputer.Hasil. Pada penelitian ini di peroleh balita yang tidak ASI Eksklusif dan perkembangan motorik yang menyimpang sebanyak 15 anak (26,8%), balita yang tidak ASI Eksklusif dan perkembangan motorik yang meragukan sebanyak 29 anak (51,8%) dan balita yang tidak ASI Eksklusif dan perkembangan motorik yang sesuai sebanyak 12 anak (21,4%). Pada balita yang ASI Eksklusif dan perkembangan motorik menyimpang sebanyak 0 anak (0%), balita yang ASI Eksklusif dan perkembangan motorik meragukan sebanyak 1 anak (2,8%), serta balita yang ASI Eksklusif dan perkembangan motorik sesuai sebanyak 35 anak (97,2%). Hal ini didukung dengan hasil uji Chi-Square dimana nilai p < nilai α yaitu p = 0,000.Kesimpulan. Terdapat hubungan signifikan antara status pemberian ASI eksklusif dengan perkembangan motorik pada anak usia 1-3 tahun di wilayah kerja puskesmas Talise tahun 2016. Kata Kunci : ASI eksklusif, Perkembangan Motorik